Electrical properties of a high-precision hexagonal spiral silicon drift detector - Li, Xiaodan; Li, Zheng; Sun, Jiaxiong; Tan, Zewen; Cai, Xinyi; Li, Xinqing; Liu, Manwen; Wang, Hongfei (Frontiers in Materials, 2023)
With the deepening and expansion of semiconductor technology and research, in order to continuously optimize the structure and performance of semiconductor detectors, a high-precision hexagonal spiral SDD is proposed in this paper. In order to obtain a more accurate spiral ring structure, this paper goes beyond the first-order formula in the Taylor expansion for calculating the radius of the spiral ring. Based on the first-order formula, the second-order formula for calculating the radius of the spiral ring is further developed and derived. The point coordinates are obtained by combining the radius, angle and ring spacing change formula to obtain a more accurate spiral ring structure. The actual number of turns is more accurate than that obtained from the first-order approximation, which better solves the problem of accurate calculation of the number of spiral rings and the structure of the spiral SDD in the existing technology, that is, the accurate calculation of the radius of the spiral ring. In order to verify the above theory, we model this new structure, use TCAD to system simulate and study its electrical properties, including potential distribution, electric field distribution and electron concentration distribution. According to the simulation results, compared with the first-order formula, the second-order formula has better electrical properties, more uniform distribution of potential, electric field and electron concentration, and clearer electron drift channel.